Unilateral pulmonary artery agenesis presenting with unilateral usual interstitial pneumonia in adulthood - Bhojwani, Nisha D.; Mistry, Dhruvin J.; Ghetiya, Jay; Gandhi , Palak (International Journal of Research in Medical Sciences, 2023)
Unilateral interstitial lung disease secondary to unilateral pulmonary artery agenesis (UPAA) is a rare anomaly due to a malformation of the sixth aortic arch of the affected side during embryogenesis. While most of the patients present in neonatal period with either cardiac anomalies or respiratory symptoms some of them can remain asymptomatic and late diagnosis is possible when suspicious presentation is noted on chest radiography. We report a case of 32-year female with a history of recurrent respiratory tract infection, who presented with cough and expectoration and the diagnosis of unilateral interstitial lung disease secondary to ipsilateral pulmonary interruption was made.